KOMIK DIGITAL SEBAGAI MEDIA PEMBELAJARAN BAHASA JAWA SUBMATERI KISAH RAMAYANA: Digital Comics as Javanese Language Learning Media Subtopic: The Story of Ramayana - Satrio Nugroho (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2023)
The utilizing of technology on an educational environment for the purpose of a learning is surely needed. It can be utilize as an learning media apllication based on technology. Digital comic as a multimedia derivative will be able to functioning as a learning media. A Javanese learning at the Center Java Junior High level considered as an important aspect for it contain lots of highly universal divine if it use correctly. Based on the reason an academical administrator should communicate a Javanese learning in an actractive way for the student to studied. In that way, students would have a new experience in the way they study. The nature of digital comic as an entertainment media and convienent to access make it an acctractively learning media. With the local genius content which in this case is Ramayana Saga be included in the media it will help to indoctrine the good values of Javanese to students. Keywords: digital comic, a learning media, Javanese